Analisis Pengaruh Media Sosial dalam Meningkatkan Engagement Pelanggan pada Perusahaan Trustmedis - Choiri, Aditya Rafiqul; Reiga Ritomiea Ariescy (Universitas Muhammadiyah Surabaya, 2024)
This research aims to examine the impact of social media in enhancing customer engagement at Trustmedis. Trustmedis is a leading Software-as-a-Service (SaaS) company that provides cloud-based digital solutions to support healthcare facilities in Indonesia, including pharmacies, clinics, community health centers, and hospitals, through the use of technology. Instagram is a popular marketing platform, especially for sales, advertising, branding, and services. The research employs a qualitative approach with a literature review method to investigate the influence of social media marketing on increasing customer engagement at Trustmedis. The researcher also utilizes industry reports as supplementary data. In this case, primary data collection was conducted through observation during an internship under the Merdeka Belajar Kampus Merdeka (MBKM) program. The study concludes that the effectiveness of social media has a significant impact on increasing engagement. If the application of social media improves, the engagement between the company and its customers automatically increases.